Practical IoT Hacking : The Definitive Guide to Attacking the Internet of Things - Chantzis, Fotios, ....-; Stais, Ioannis, ....-; Calderon, Paulino, ....-; Deirmentzoglou, Evangelos, ....-; Woods, Beau, ....- (usa : Pollock, 2021)
Geared towards security researchers, IT teams, and penetration testers, application testers, developers, and IT administrators, this book teaches readers how to get started with hacking Internet connected devices. Readers dig deep into technical (and related legal) issues, as they learn what kinds of devices to use as hacking tools and which make the best targets. The authors, all experts in the field, cover the kinds of vulnerabilities found in IoT devices, explain how to exploit their network protocols, and how to leverage security flaws and certain hardware interfaces found in the physical devices themselves.
Description based on publisher supplied metadata and other sources.
Keywords: Electronic books; hacking; internet of things